Analysis of Information Publication Management on the @SEMARAS_SIA Account Based on The Circular Model of SOME Theory - Muhammad, Anshori (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2023)
This study aims to investigate the social media management in the information publication carried out by the Instagram account @semaras_sia. It employs a qualitative descriptive methodology with data collection techniques such as observation, interviews, and documentation. The findings reveal four stages in social media management: (1) In the Share stage, the subjects engage in three crucial aspects, namely participation, connection, and trust-building. (2) In the Optimize stage, the subjects are not adequately involved in authentic communication. (3) In the Manage stage, the subjects conduct media monitoring, real-time interaction, and respond promptly. (4) In the Engage stage, influencers or communities are not consistently involved in the information publication. The social media management by the subjects does not align with The Circular Model of SOME, resulting in suboptimal performance in information publication through social media channels.